Principal component analysis of the oxidative stress, inflammation, and dyslipidemia influence in patients with different levels of glucoregulation: Oxidative stress in (pre)diabetes - Klisic, Aleksandra (Journal of Medical Biochemistry, 2022)
Objective: The aim of the study was to explore the mutual relationship between oxidative stress, inflammation and metabolic biomarkers in subjects with prediabetes (PRE), newly diagnosed type 2 diabetes patients (NT2D) and overt type 2 diabetes (T2D) using principal component analysis (PCA) as a thorough statistical approach.Patients and Methods: Glycated hemoglobin,  lipid parameters, inflammation (IL-6, CRP and fibrinogen) and oxidative stress markers [pro-oxidants (AOPP, PAB, TOS) and antioxidants (PON1, tSHG, TAS)] were measured. PCA was applied to explore the factors most strongly influencing glucoregulation.Results: A total of 278 subjects were enrolled: 37 PRE, 42 NT2D and 99 T2D, who were compared with 100 healthy subjects as a control group (CG). PCA emphasized 4 different factors explaining 49% of the variance of the tested parameters: Oxidative stress-Dyslipidemia related factor (with positive loading of TG and tSHG, and with negative loading of HDL-c and TAS), Dyslipidemia related factor (i.e., total cholesterol and LDL-c, both with positive loading), Anthropometric related factor (i.e., waist and hip circumference, both with positive loading) and Oxidative stress-Inflammation related factor (i.e., PAB, fibrinogen, and CRP, all with positive loading). Out of these 4 factors, only Oxidative stress – Dyslipidemia related factor showed a significant predictive capability towards poor glucoregulation. An increase in this factor by one unit showed a 1.6 times higher probability for poor glucoregulation.Conclusion: Redox disbalance (determined with lower TAS and higher tSHG), in addition to higher TG and lower HDL-c were associated with poor glucoregulation.